The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/schbul/sby113
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Count Is Associated With Reduced Gray Matter and Enlarged Ventricles in First-Episode Psychosis

Abstract: Although there is recent evidence that cells from the peripheral immune system can gain access to the central nervous system in certain conditions such as multiple sclerosis, their role has not been assessed in psychosis. Here, we aimed to explore whether blood cell count was associated with brain volume and/or clinical symptomatology. A total of 218 participants (137 first-episode psychosis patients [FEP] and 81 healthy controls [HC]) were included in the study. For each participant, a T1 structural image was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 65 publications
7
28
1
Order By: Relevance
“…Of note, because we can only derive proportion of cell types from whole blood DNA methylation data, and not actual counts, an increase in one or more cell types must be balanced by a decrease in one or more other cell types and an apparrent change in the proportion of one specific cell type does not mean that the actual abundance of that cell type is altered. Despite this, the results from DNA methylation-derived cell proportions are consistent with previous studies based on empirical cell abundance measures which have reported increased monocyte counts 67,68 , increased neutrophil counts 69,70 , increased monocyte to lymphocyte ratio 71,72 and increased neutrophil to lymphocyte ratio 71,73 in both schizophrenia and FEP patients compared to controls. Studies have also shown that higher neutrophil counts in schizophrenia patients correlate with a greater burden of positive symptoms 69 suggesting that variations in the number of neutrophils is a potential marker of disease severity 72 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Of note, because we can only derive proportion of cell types from whole blood DNA methylation data, and not actual counts, an increase in one or more cell types must be balanced by a decrease in one or more other cell types and an apparrent change in the proportion of one specific cell type does not mean that the actual abundance of that cell type is altered. Despite this, the results from DNA methylation-derived cell proportions are consistent with previous studies based on empirical cell abundance measures which have reported increased monocyte counts 67,68 , increased neutrophil counts 69,70 , increased monocyte to lymphocyte ratio 71,72 and increased neutrophil to lymphocyte ratio 71,73 in both schizophrenia and FEP patients compared to controls. Studies have also shown that higher neutrophil counts in schizophrenia patients correlate with a greater burden of positive symptoms 69 suggesting that variations in the number of neutrophils is a potential marker of disease severity 72 .…”
Section: Discussionsupporting
confidence: 88%
“…Despite this, the results from DNA methylation-derived cell proportions are consistent with previous studies based on empirical cell abundance measures which have reported increased monocyte counts 67,68 , increased neutrophil counts 69,70 , increased monocyte to lymphocyte ratio 71,72 and increased neutrophil to lymphocyte ratio 71,73 in both schizophrenia and FEP patients compared to controls. Studies have also shown that higher neutrophil counts in schizophrenia patients correlate with a greater burden of positive symptoms 69 suggesting that variations in the number of neutrophils is a potential marker of disease severity 72 . Our sub-analysis of treatment-resistant schizophrenia, which is associated with a higher number of positive symptoms 65 , found that the increase in granulocytes was primary driven by those with the more severe phenotype, supporting this hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…A recent cross-sectional study combined magnetic resonance imaging of the brain and differential blood analyses and observed significantly increased neutrophil granulocytes in FEP patients ( n = 137) vs controls ( n = 81). 9 Neutrophil granulocytes were associated with reduced total brain gray matter. Their counts correlated with clinical symptom severity, namely total, positive and general Positive and Negative Syndrome Scale (PANSS) subscores, but not with PANSS negative scores.…”
Section: Introductionmentioning
confidence: 99%
“…The probable mechanism of the observed changes in psychosis may be associated with inflammatory disorders, dysregulation of the immune system [3,10], neurodevelopmental disorders, including genetic abnormalities, i.e., 22q11.2 (22q11DS) deletion [11,12], or neutrophil functioning in the severe forms of mental disorders [10]. Their higher levels strongly correlate with positive clinical symptoms, constituting a promising marker of disease progression [13]. In turn, the mentioned genetic disorders (22q11DS) are the cause of the limited growth of axons and dendrites, which impair the integrity of mitochondria and functioning of synapses in productive neurons [11].…”
mentioning
confidence: 99%